Assessing the digital competencies and transformational leadership of school administrators: the case of Adana - Ersoy, Abdurrahman; Penpece Demırer, Dılek (Frontiers in Education, 2026)
IntroductionIn the context of the rapid digitalization of education, developing and sustaining the digital competencies of school administrators has become a crucial factor.ObjectiveThe study aims to examine the digital competencies and transformational leadership of school administrators. This study examined whether school administrators’ digital competency levels differed by gender and age and explored the relationship between their transformational leadership characteristics and digital competencies.MethodologyA questionnaire consisting of three sections was employed in the study. The study sample consisted of 395 school administrators working in public schools under the Ministry of National Education in Adana, Turkey, during the 2022–2023 academic year.Results and conclusionThe study revealed that while school administrators’ digital competency levels did not differ significantly by gender, they varied significantly across age groups. A positively moderate significant relationship was identified between administrators’ levels of transformational leadership and digital competencies. This study contributes to the growing body of literature on digital competencies and provides valuable insights for policymakers and professional development initiatives.